Pengaruh Gradasi Pasir Terhadap Kekuatan Tekan dan Penyerapan Paving Blok Geopolimer - Sandri L. Sengkey; Geertje E. Kandiyoh; Stefani S. Peginusa; Dwars Soukotta (Jurnal Serambi Engineering, 2024)
The quality of paving blocks is greatly influenced by many factors, one of which is sand as the constituent material. Sand has various types and different gradations based on grain size distribution. This difference in sand gradation is the focus of research to determine the effect of sand gradation on the compressive strength and absorption of geopolymer paving blocks made from fly ash. The geopolymer block paving mixture is made with a composition of 10M NaOH, a Na2SiO3/NaOH ratio of 2.5, an alkali activator/FA solution ratio of 0.4 and curing at ambient temperature. The test results show the influence of sand gradation on compressive strength and absorption. The highest compressive strength and lowest absorption values were obtained in the Z3-BP and Z2-AB mixtures. There is a relationship between compressive strength and absorption. The smaller the paving absorption value, the greater the compressive strength.